Python : object-oriented programming. (Packt Publishing, 2022)
Python is a fantastic OOP language that lets you use functional and OOP paradigms. Python offers several benefits compared to other programming languages like Java, C++ or R. It is a dynamic language, with high-level data types. Python is easier to learn for beginners as its codes are more readable and intuitive. This course is designed to take you through the fundamentals of OOPs and understanding how it works. During this course, you will learn about important concepts such as classes, objects, abstraction, method overloading, and inheritance in sufficient detail. The course will also take you through the concepts of objects and attributes, mathematical operators, callable functions, encapsulation, inheritance and method resolution comprehensively. The course explains the OOP paradigm and lets you create class hierarchies using the OOP design process. By the end of the course, you will be able to design and implement Python programs for complex issues and make good use of the OOP features like classes and inheritance and apply your knowledge completing assignments that simulate real-world scenarios. What You Will Learn Create class hierarchies using the object-oriented design process Understand the difference between class and instance variables Make an object indexable, callable, and comparable Design and implement Python programs for complex problems Put to code the language features such as classes and inheritance Tackle complex code with OOP paradigm, design, and implementation Audience This course provides new developers who know Python basics to expand their knowledge and developers and learners who wish to learn OOP in Python. Developers involved with game development, GUI programming, AI, machine learning, and other computed automation can benefit from this course. The concepts and techniques can be applied to other programming languages, so intermediate-level developers wishing to advance their programming skillsets can also learn from this course for career advancement. To get the most from this course, you need to be an intermediate-level programmer in Python. About the Author Simon Sez IT: Simon Sez IT has offered technical courses since 2008 for individuals, small businesses, and Fortune 500 companies with thousands of employees who can benefit from the easy-to-learn and hands-on software training. It offers over 8000 video tutorials on a range of software programs. Simon Sez IT ensures stress-free eLearning and enhanced employee productivity--whether you implement new software or a technological upgrade in your work environment. With over 600,000 students from 180 countries, Simon Sez IT is the preferred online learning choice for individuals and businesses worldwide.